Actions needed to halt deforestation and promote climate-smart agriculture - Wollenberg, Eva Karoline; Campbell, Bruce M.; Holmgren, Peter; Seymour, F.; Sibanda, Lindiwe Majele; Braun, Joachim von (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Integrated action across Reduced Emissions from Deforestation and forest Degradation (REDD+) and agriculture is necessary to achieve mitigation and food security outcomes.